PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN PROGRAM POWERPOINT BAGI GURU SMP ISLAM TERPADU NW TEKO - Khulaimi, Muhammad; Nukman, Nukman; Rosyidi, Ahmad Zuhri (INSANTA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
This Community Service activity is entitled Training on Making Interactive Learning Media with the Powerpoint Program for Teachers of Integrated Islamic Middle School NW Teko. The aim of this activity is to develop multimedia learning media by utilizing the Powerpoint program which will be developed and implemented for SMP teachers with the hope that it will provide new insights in making learning media, considering the ability of this program in terms of making animations for interesting multimedia learning media in a relatively easy way. The method of implementing this activity is by providing training to teachers by providing training materials and followed by practice. The result of this activity is that the training participants have been able to apply this Powerpoint program to create learning media such as Entering Text and Images, Entering Sound and Video, Creating backgrounds, Setting effects, orders and timings, Creating Hyperlinks between slides, Creating Hyperlinks to URLs.